Ekstraksi Tanin dari Buah Balakka (Phyllanthus emblica L.) dengan Bantuan Microwave: Pengaruh Daya Microwave, Perbandingan Massa Kering Terhadap Jumlah Pelarut Etil Asetat - Iriany; Angkasa, Hendri; Namira, Cut Annisa (Jurnal Teknik Kimia USU, 2021)
Tannins are phenolic compounds with considerable abundance in nature. In this study, the extraction of Indian gooseberry fruit was performed using Microwave Assisted Extraction (MAE) method with ethyl acetate as solvent. Two grams of Indian gooseberry fruit were extracted for 1 minute with variable microwave power operation (100, 180, 300, 450 and 600) W. The experiment is continued at the power that gave the highest yield of tannin withÂ  variable ratio sample to solvent (1/10, 1/20, 1/30, 1/40 and 1/50) g/mL. Total tannins in the extract were analyzed using UV-Vis Spectroscopy method to find the yield of tannin. Functional groups that were contained in the extract were analyzed using Fourier-Transform Infrared Spectroscopy (FTIR) method. The results of this study indicate that the extract contains tannins in qualitative tests with gelatin and FeCl3 as well as in FTIR analysis. The highest yield of tannin was 36.86 mg/g which was obtained under conditions of power 100 W and ratio sample with ethyl acetate 1/50 g/mL.